Longer-Run Economic Consequences of Pandemics - Jordà, Òscar; Singh, Sanjay R.; Taylor, Alan M. (The Review of Economics and Statistics, 2022)
Abstract What are the medium- to long-term effects of pandemics? Do they differ from other economic disasters? We study major pandemics using rates of return on assets stretching back to the fourteenth century. Significant macroeconomic after-effects of pandemics persist for decades, with rates of return substantially depressed. The responses are in stark contrast to what happens after wars. Our findings also accord with wage and output responses, using more limited data, and are consistent with the neoclassical growth model: capital is destroyed in wars but not in pandemics; pandemics instead may induce more labor scarcity or more precautionary savings, or both.